Nilai Pendidikan Karakter dalam Novel Bulan Terbelah di Langit Amerika - NFN Lastaria; NFN Widya (Balai Bahasa Kalimantan Tengah, 2019)
A good novel is a novel that has much benefits and good values. A novel written by Hanum Salsabiela Rais, Bulan Terbelah di Langit Amerika, is one of several good novels. Therefore, researchers chose the novel as a source. This is a qualitative and descriptive paper. From the analysis there are nineteen character values in the novel, namely (a) religious, (b) honest, (c) responsible, (d) healthy lifestyle, (e) discipline, (f) hard work, (g) self-confidence, (h) logical thinking (critical, creative, and innovative), (i) independent, (j) curios, (k) self-conscious, (l) polite, (m) democratic, (n) nationalist, (o) pluralist, (p) intelligent, (q) helpful, (r) resilient, and (s) action oriented.